Preliminary Study of Green Material for Green Building in Bali - Ni Wayan Meidayanti Mustika; Acwin Ngakan Ketut Dwijendra (International Journal of Engineering and Emerging Technology, 2021)
The definition of green materials is building materials that are environmentally friendly, do not have a negative impact on building users, and are sustainable. Green Material is one of the criteria in the green building assessment parameters that will support energy efficiency goals. Understanding green materials and their availability for their demands in Bali is important to align the growth of green buildings in Bali with the potential and problems of material supply. This paper aimed at conducting an initial preliminary study of the limitation and opportunities for the use of sustainable building materials according to the green building principle approach in Bali. The method used is descriptive method that is reinforced by literature review techniques related to the context of the discussion . Buildings in Bali, when viewed from the use of building materials, carry very distinctive design and appearance characteristics. The selection of green materials in Bali will be influenced by the demands of the requirements for implementing Balinese architecture in buildings, restrictions on material procurement due to location, material legality references and ecolabel certification documents and opportunities for using smart and advanced materials without losing the character of Balinese building architecture.